Representations of the Life-giving Spring feast in Romanian iconography - Abrudan, Ioan O. (HTS teologiese studies, 2021)
This article explores the development of the theme of the Life-giving Spring in Byzantine iconography. The path towards its establishment was initiated at the moment when a representation rule, an original convention was set. Thereafter, because of its diffusion in time and space, the theme became enriched by particular mentalities and sensibilities of the epochs and the communities that adopted it as a form of devotion for the Virgin Theotokos. As a result, the representations we have known so far are extremely varied.Contribution: The final purpose of this approach, as well as its contribution, is to highlight the diverse unity of the iconographic tradition and illustrate both the evolution of the theme in the painting of Romanian church artists and its gradual refinement through the incorporation of diverse nuances and new perspectives.